(untitled) (Minerva, 2019)
The Epistularium of Braulio, bishop of Saragosse († 651), presents us with valuable evidence of some of the developments in the use of demonstrative adjectives and pronouns in the VIIth. century. In this text, which is a highly elaborated piece of writing, we can trace, always within the boundaries of the classic usage, the origin of some of the tendencies in the frequency and functions of the demonstratives that would later on shape the paradigm of the Romance article.